The effect of imperfect mixing on gas-liquid reactions: Linkage between liquid-film and bulk liquid - Saidina Amin, Nor Aishah; Parulekar, Satish J. (1997)
The extensive literature on gas-liquid reaction has, with a few exceptions, been devoted to reactions that are considered to be completed entirely in liquid-film or bulk liquid for the sake of simplification of modeling and design. A different perspective for modeling of gas-liquid reactions is presented here. The two-way linkages between liquid-film and bulk liquid, largely ignored previously, are properly accounted for in the present approach. This is especially essential in situations where the gas and liquid phases are not perfectly mixed (situations very frequently encountered in industrial operations), since the composition of the liquid in the film and the bulk both vary with axial position in the reactor. A first-order irreversible reaction, a perfectly mixed liquid phase, non-perfect mixing in the gas phase are considered as an example. The effects of transport and kinetic parameters on reactor performance are presented via appropriate numerical illustrations. An unwarranted confinement of the liquid phase reaction to either portion of the liquid phase is shown to lead the incorrect design and erroneous prediction of performance of gas-liquid reactors.